History and Perspectives of Adult Education and Professional Teacher Education: Between complicity, distance, and recognition - Maubant, Philippe; Roger, Lucie; Lejeune, Michel; Caselles-Desjardins, Brigitte; Gravel, Nicole (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
This text is divided into three broad sections. The first section will elaborate the figure of professionalization, which today appears to be the target of professional training policies. It also seems to be considered a means and thus a guarantee of the professional aim of proposed training. On what ideological and pedagogical presuppositions is this professionalization based? The second figure embodying professional training contexts is that of knowledge. What knowledge is present in the professional training of teachers? Is it involved in professionalization processes? If so, in what ways? To what extent does the tone given to professionalization – whether in connection with the objective of instruction, socialization, or qualification – determine a specific sense for Knowledge and for the knowledge defined and articulated in professional teacher training? The third symbolic figure of professional training is that of the school-life relationship. Where does professional training begin and end? What are its territories? Can it exceed the usual territories and hence the expertise expected of a professional? By examining these three forms, we hope to offer the reader a new approach to professional teacher training inspired by a reminder of the aims and values of adult education.